The Influence of Chloride Ion Concentration and Short Immersion Time on the Corrosion Behavior of C11000 Copper Alloy - Priyotomo, Gadang; Anam, Ahsonul; Maldini, Noviar Rizky (Program Studi Teknik Mesin Universitas Pamulang, 2025)
The effect of various chloride ion concentration (0 %, 1 %, 2 %, 3%, 4% and 5 % NaCl solution) on the corrosion behavior of the C1100 copper alloy was investigated with the immersion test (weight loss method). The effect of various immersion periods was also examined up to 14 days. After conducting immersion test, metal surfaces were observed with an optical microscope and the SEM analysis. The product of corroded copper was characterized using Energy Dispersive Analysis of X-rays (EDAX). On the basis of results, the magnitude of corrosion rate is higher in increasing the chloride concentration and immersion period, respectively. The increase of chloride concentration causes the copper oxide layer to become porous and cracked compared to without chloride addition. The reduction in the integrity of the copper protective layer took place due the presence of chloride ion.